A Case Report: MRI versus Ultrasonography in Abdominal Pregnancy, Which One is Better? - Rahman, Luthfi; Reswari, Arnova; Pribadi, Adhi (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2023)
Abdominal pregnancy is a rare potentially life-threatening form of ectopic pregnancy. First trimester sonography is very useful to identify an abdominal pregnancy earlier. However, cases of undiagnosed abdominal pregnancy at second and third trimesters are still reported in obstetric practice. Abdominal pregnancy is often missed during routine ultrasound examination that has classical findings such as the absence of myometrial tissue between the maternal bladder and the pregnancy, an empty uterus, poor visualization of the placenta, oligohydramnios, and abnormality of fetal lie. Magnetic Resonance Imaging (MRI) has been reported as the best abdominal pregnancy detection modality in a later gestational age due to its ability in detailing vascular and placental organ invasion.The reporting of a case of a patient with an abdominal pregnancy involves a diagnosis using abdominal ultrasound in the second trimester. A 38-year-old woman was admitted to RSUP Dr. Hasan Sadikin Bandung with suspected abdominal pregnancy at gestational age of 28 weeks. Due to unclear clinical manifestation, the diagnosis of abdominal pregnancy was not detected and there was a plan for vaginal termination of pregnancy by misoprostol induction in the hospital before. The patient complained about progressive abdominal pain and difficult of defecation for 2 months before and this condition worsened in the last 4 days. Ultrasound examination in RSHS revealed that there were one living fetus, extra-uterine pregnancy with estimated fetal weight of 664 grams, fetal heart rate (+), and transverse breech presentation. Congenital abnormality was difficult to assess due to oligohydramnios. MRI was performed and showed intra-abdomen pregnancy with one living fetus, breech presentation, and intact amniotic membrane with oligohydramnios which was superior to the uterus and attached along the anterior aspect of uterus. The placenta had the size os 11.52 x 7.02 x 13.07 cm, was diffusely heterogenous in shape, on the right superoanterolateral wall of the gestational sac, and seemed to be attached to the right anterior abdominal wall and part of the intestine in the superior part while no placental adherence was seen. The patient was successfully treated with exploratory laparotomy with complete removal of the fetus and placenta. This case was reported to compare the advantage of MRI and ultrasound examination in detecting abdominal pregnancy, especially in late gestational age.Laporan Kasus: MRI dan Ultrasonografi pada Kehamilan Abdomen, Manakah yang Lebih Baik?AbstrakKehamilan abdomen adalah bentuk kehamilan ektopik yang jarang terjadi dan memiliki potensi mengancam jiwa. Pemeriksaan ultrasonografi (USG) pada trimester pertama berguna untuk mengidentifikasi kehamilan abdominal lebih awal. Namun, kehamilan abdomen yang tidak terdiagnosis masih sering dijumpai pada trimester kedua dan ketiga. Tanda klasik kehamilan abdomen sering terlewatkan oleh operator pada saat pemeriksaan USG rutin. Magnetic Resonance Imaging (MRI) merupakan modalitas terbaik untuk mendeteksi kehamilan abdomen pada usia kehamilan yang lebih tua karena mampu melihat invasi pembuluh darah dan organ plasenta secara lebih detail.Kami melaporkan sebuah kasus mengenai seorang wanita 38 tahun yang terdeteksi memiliki kehamilan abdominal pada usia kehamilan 28 minggu pada pemeriksaan USG saat perawatan di RSHS. Manifestasi klinis pada pasien tidak spesifik sehingga diagnosis kehamilan abdominal terlewati dan sempat diberikan rencana terminasi kehamilan pervaginam di rumah sakit sebelumnya. Pemeriksaan USG menunjukkan terdapat satu janin hidup dan terletak luar rahim. Kemudian pasien diputuskan menjalani pemeriksaan MRI, ditemukan adanya kehamilan intra abdomen dengan satu janin hidup, presentasi bokong, dan plasenta berbentuk heterogen difus, di dinding superoanterolateral kanan kantung kehamilan, melekat pada dinding abdomen anterior kanan dan bagian usus di bagian superior, dan tanpa adanya perlengketan plasenta. Pasien ditangani dengan laparotomi eksplorasi dengan pengangkatan janin dan plasenta secara lengkap. Kasus ini bertujuan membandingkan keunggulan pemeriksaan MRI dan USG dalam mendeteksi kehamilan abdominal, terutama pada usia kehamilan lanjut.Kata kunci: ultrasonografi, MRI, kehamilan abdominal